The Influence of Biotechnology-Based Bio entrepreneurship Learning Model on the Enthusiasm Level and Entrepreneurial Personality of High School Students in Sukabumi Regency - Mursyida, Wilda Waliam; Juhanda, Aa; Rukmana, Endris; Ramdhan, Billyardi (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
This research is motivated by the low level of student enthusiasm towards entrepreneurship due to the lack of activities that foster entrepreneurial personality. The research aims to examine the influence of biotechnology-based bio entrepreneurship on students' enthusiasm and entrepreneurial personality. A quasi-experimental design with a non-equivalent control group was used, involving class X students at SMAN 1 Cireunghas, Sukabumi district. Questionnaires were administered to collect data. Results showed that in the experimental group, 81% of students demonstrated a high level of enthusiasm with an N-Gain score of 0.81, increasing from a pretest average of 73.13 to a posttest average of 93.7. Regarding entrepreneurial personality, 79% of students exhibited high scores, with an N-Gain of 0.79, improving from a pretest average of 82.97 to a posttest average of 97.3. Hypothesis testing revealed significant differences between the experimental and control groups, with a significance level of 0.003 for enthusiasm and 0.020 for entrepreneurial personality (p < 0.05). Thus, biotechnology-based bio entrepreneurship positively influences both the enthusiasm and entrepreneurial personality of students.